Переобразуйте в многочлен выражение: (11х+у)^2= (3c-d)^2= (-m-2b)^2= (-2a+5c)^2 =

Андрей12385 Андрей12385    1   08.03.2019 11:50    2

Ответы
1246881 1246881  24.05.2020 05:57

(11х+у)^2= 121х^2 + 22xy + y^2

(3c-d)^2= 9c^2 - 6cd + d^2

(-m-2b)^2= -(m+2b)^2= -(m^2 + 4mb + 4b^2) = -m^2 - 4mb - 4b^2

(-2a+5c)^2 = (5c-2a)^2 = 25c^2 - 20ac + 4a^2

ПОКАЗАТЬ ОТВЕТЫ
Altama Altama  24.05.2020 05:57

1, =121х^2+22xy +y^2

2. =9c^2 - 6dc + d^2

3. = m^2 + 4mb + 4b^2

4. = 4a^2 - 20ac  + 25c^2 

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра